The Effect of Carbon Source Addition of Molasses With Different Doses in Biofloc Systems toward Growth and Survival Rate of Red Tilapia (Oreochromis sp) in Brackish Water Media - Manik, Retno Aprita; Rusliadi, Rusliadi; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on August to September 2017 in the Technical Services Unit (UPT) of Hatchery, Marine & Fisheries Faculty, Universitas Riau, Pekanbaru. The purpose of this study was to determine the best dose of carbon source addition of molasses in biofloc system toward growth and survival rate of red tilapia in brackish water media. The method in this study was the experimental method of completely randomized design (CRD) with one factor, four treatments and three replications. P1: carbon source addition by 50 ml /m3 of molasses dose, P2: carbon source addition by 100 ml /m3, of molasses dose, P3: carbon source addition by 150 ml / m3 of molasses dose, and P4: carbon source addition by 200 ml /m3 of molasses dose. The results showed that the best treatment of carbon source additionwas at the 200 ml/m3 (P4)of molasses dose. The specific growth rate was 4.25%, 132.29% of feed efficiency, feed conversion ratio (FCR)was 0.75, survival rate (SR) was 81.67%, floc volume was 4.61 ml/l. The qater quality parameters consists of temperature was arround 26-310C, DO was 4.13 to 6.83 mg/ l, pH was 7 to 7.6, 16-20 ppt of salinity and ammonia was from 0.0718 to 0.3625 mg/ l. Keywords: Molasses, Biofloc, Red Tilapia (Oreochromis sp)